1981
DOI: 10.1007/bf02899449
|View full text |Cite
|
Sign up to set email alerts
|

Production and use of natural antioxidants

Abstract: We have developed a new industrial process for obtaining natural antioxidants from spices and other vegetables by primarily adapting mechanical and physical treatments. Rosemary, sage, paprika, nutmeg and cocoa shells have been submitted to a mechanical treatment (micronization), and the finely powdered material was extracted with an edible vegetable oil, i.e., groundnut. The antioxidant dissolved in the lipid phase was collected by two‐stage falling film molecular distillation to separate the lipid phase to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
11

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 8 publications
1
45
0
11
Order By: Relevance
“…The presence of phenolic compounds in the Pouteria extracts can explain, at least in part, the antioxidant and radical scavenging activities presented by the more polar extracts and fractions (Rice-Evans et al, 1996). In addition, lupeol, ursolic acid and others triterpenes also have demonstrated capacity to intercept free radicals (Bracco et al, 1981;Saleem et al, 2001).…”
Section: Biological Activities Of Pouteria Speciesmentioning
confidence: 99%
“…The presence of phenolic compounds in the Pouteria extracts can explain, at least in part, the antioxidant and radical scavenging activities presented by the more polar extracts and fractions (Rice-Evans et al, 1996). In addition, lupeol, ursolic acid and others triterpenes also have demonstrated capacity to intercept free radicals (Bracco et al, 1981;Saleem et al, 2001).…”
Section: Biological Activities Of Pouteria Speciesmentioning
confidence: 99%
“…The antioxidant properties of aromatic plants and spices Antioxidant capacity and biological activity of essential oil and methanol extract of Hyptis crenata Pohl ex Benth have been indicated as effective in delaying the lipid peroxidation of foods (Bracco et al, 1981;Kramer, 1985;Lagouri et al, 1993;Souza et al, 2007). Tsimidou and Boskou (1994) observed that between the herbs and spices extensively studied, the plants belonging to the Lamiaceae family have significant antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic antioxidants such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA) and propyl gallate (PG) have been used as food additives to inhibit the actions of toxic and carcinogenic substances (Chang et al, 1977). Natural antioxidants from natural foods such as herbs (Bracco et al, 1981;Inatani et al, 1982;Pizzocaro et al, 1994), vegetables (Tsushida et al, 1994;Vinson et al, 1998), fruits (Nogata et al, 1996;Wang et al, 1996), oilseeds Fukuda et al, 1985;Medina et al, 1999), spices Chipault et al, 1995;Kramer, 1995;Hettiarachchy et al, 1996), green tea (Amarowicz & Shahidi, 1996) and cereals (Asamari et al, 1996;Maillard et al, 1996;Hendelman et al, 1999) have been studied, and some of them, such as ascorbate and tocopherols, are currently used in a variety of food products. a-Tocopherol, a form of vitamin E, is widely used as a natural antioxidant.…”
mentioning
confidence: 99%